2019
DOI: 10.1177/0959651819864851
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Optimization of diesel engine performance and emission parameters operating waste tire pyrolysis oil–diesel blends using response surface methodology

Abstract: Nowadays, the waste products as alternative fuels for diesel engines have become vital importance because of the increase in energy consumption, the rigid emission standards and the reduction in fossil fuel reserves. Waste tire pyrolysis oil is an important alternative fuel for the evaluation of waste. The aim of this study is to optimize the engine parameters which are responsible for the emission as well as engine performance analysis in terms of waste tire pyrolysis oil–diesel blends in a diesel engine by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(17 reference statements)
0
0
0
Order By: Relevance
“…Recently, Uslu [169] has attempted to optimise a blend consisting of low viscosity TPO and DF, using legacy engine experiments.The optimised parameters were TPO fraction and injection pressure. It was found that increasing TPO admixture content above 30 % lead to a rapid increase in NOX emissions, whereas TPO's effect on NOX was negligible when admixture was below 30 %.…”
Section: Tests With Refined Tpo On Basic Engine Platformsmentioning
confidence: 99%
“…Recently, Uslu [169] has attempted to optimise a blend consisting of low viscosity TPO and DF, using legacy engine experiments.The optimised parameters were TPO fraction and injection pressure. It was found that increasing TPO admixture content above 30 % lead to a rapid increase in NOX emissions, whereas TPO's effect on NOX was negligible when admixture was below 30 %.…”
Section: Tests With Refined Tpo On Basic Engine Platformsmentioning
confidence: 99%